Increased the specificity and sensitivity of monospecific antibody against host cell protein (HCP) in quality control of hepatitis B recombinant vaccine - Hosseini, Seyedeh Marzieh; Tabaraei, Bahman; Hadadian, Shahin; Yavari, Fereshteh; KamaliJamil, Razieh; Shayestehpour, Mohammad; Nejati, Mahdi; Vaez, Javad (Archives of Advances in Biosciences, 2011)
One of the most important aspects in recombinant biologic production, based on GMP rules, is the accuracy of final product quality control, especially assessment of host cell macromolecules contamination rate in final product. The purification requirement can be eliminated when the yeast cell containing the recombinant protein is used as a host cell. It is possibile that the final product contaminated to the host cell protein during purification stages of HBsAg (HBV vaccine). The protein purification costs depend on the purification procedures required. Nowadays several companies produce commercial kits for identification and assessment of host cell protein contamination based on ELISA and Western blotting methods. But high prices, difference in sensitivity and lack of easy access to these kits sometimes create problems. So, in this study, two methods of Ammonium sulphate and caprilic acid precipitation technique were used separately for IgG purification. The results showed that IgG purification increased by 97% in caprylic acid method, compared with only a 77% increase in ammonium sulphate method. There were also significant differences in specificity and sensitivity between our standardized ELISA technique and using commercial kit (Cygnus CHO HCP).